Bi-currency versus single-currency targeting: lessons from the Russian experience - Vladimir Sokolov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2010)
This paper examines the impacts of the 2005 shift in Russian exchange rate policies from single-currency to bi-currency basket targeting on domestic interest rates and sovereign risk premium dynamics. The policy shift disconnected domestic interest rates from US dollar-denominated interest rates, replacing them with a growing positive relationship with the dual-currency basket (USD-EUR) adopted by the Central Bank of Russia, as well as a synthetic interest rate composed of the US dollar LIBOR and the euro LIBOR. The paper also considers the insulating properties of Russian basket targeting policies during the recent global liquidity crisis. I present evidence that the Russian MosIBOR rate was negatively related to the US dollar LIBOR rate and positively related to the synthetic USD-EUR rate during the "decoupling" stage of the crisis. Even with the steep quantitative easing of the US Fed during this period, the finding suggests the Russian money market was more in sync with ! the monetary policies of the euro area. The central conclusion here is that, in conditions of managed floating exchange rate policies and liberalized capital accounts, the relationship between a country's domestic interest rates and their foreign counterparts depends on the de facto operating target of the central bank of this country, whether it is a single currency or a basket.
URN:NBN:fi:bof-201408071917
Keywords: F31; F33; 330; exchange rate policy; basket targeting; sovereign CDS; decoupling